Wissenschaftliches Arbeiten im Studienbereich Deutsch als Fremdsprache: Ein Arbeitsbuch zu ausgewählten Aspekten des Verfassens von Abschlussarbeiten - Jazbec, Saša; Löwenkamp, Sarah; Kacjan, Brigita (2023)
Academic Writing in the Field of German as a Foreign Language: A Workbook on Selected Aspects of Thesis Writing. At the end of their studies, students in the Department of German Studies are required to write a thesis, for which various topic-related skills in the field of empirical research and the writing of academic texts are required. By reading and writing academic and specialized texts, students are supposed to acquire this specific set of skills in German. However, it is often found that there are certain, recurring difficulties which delay the completion of their studies. This workbook is not intended to provide a systematic overview of all aspects of writing scientifically and professionally correct theses, but to address those aspects that have proven particularly difficult in recent years. By solving the tasks offered in this monograph, students can improve their academic writing. The theoretical impulses are relevant and applicable already during their studies but are especially useful right before and during the writing of the thesis.
Keywords: academic writing; german; research field of german as a foreign language; writing style; in-text citation